Microtubule-dependent Organization of Vaccinia Virus Core–derivd Early mRNAs into Distinct Cytoplasmic Structures - Mallardo, Massimo (The American Society for Cell Biology, 2001)
Vaccinia virus (vv) early transcription can be reconstituted in vitro from purified virions; in this assay mRNAs are made inside the viral core and subsequently extruded. Although the in vitro process has been extensively characterized, relatively little is known about vv early transcription in vivo. In the present study the fate of vv early mRNAs in infected HeLa cells was followed by BrUTP transfection and confocal and electron microscopy. The extruded vv early mRNAs were found to be organized into unique granular cytoplasmic structures that reached a size up to 1 μm. By EM these structures appeared as amorphous electron-dense cytoplasmic aggregates that were surrounded by ribosomes. Confocal images showed that the RNA structures were located some distance away from intracellular cores and that both structures appeared to be aligned on microtubules (MTs), implying that MT tracks connected mRNAs and cores. Accordingly, intact MTs were found to be required for the typical punctate organization of viral mRNAs. Biochemical evidence supported the notion that vv mRNAs were MT associated and that MT depletion severely affected viral (but not cellular) mRNA synthesis and stability. By confocal microscopy the viral mRNA structures appeared to be surrounded by molecules of the translation machinery, showing that they were active in protein synthesis. Finally, our data suggest a role for a MT and RNA-binding viral protein of 25 kDa (gene L4R), in mRNA targeting away from intracellular cores to their sites of cytoplasmic accumulation.